Wormwood graphite encapsulated thermally conductive phase change particles and thermal interface materials and preparation methods
By combining hydrophilic modified worm graphite with phase change material, a thermal interface material with high thermal conductivity and phase change temperature regulation function was prepared, which solved the problems of thermal conductivity bottlenecks of traditional materials and leakage of phase change materials, and achieved the formation of a dual continuous thermal conductivity network and the improvement of material stability.
Patent Information
- Application Number
- CN202211121216.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-09-15
AI Technical Summary
There are bottlenecks when traditional thermal interface materials improve thermal conductivity, and the leakage of phase change materials and low thermal conductivity during the phase change process affects their effect stability.
By combining hydrophilic modified worm graphite with organic phase change material, the thermally conductive phase change particles are prepared by vacuum-assisted impregnation technology, and mixed with the thermally conductive filler and liquid polymer to form a thermal interface material with high thermal conductivity and phase change temperature regulation function.
It effectively solves the problem of uneven adsorption of expanded graphite and phase change materials, forms a dual continuous thermal conductivity network, significantly improves thermal conductivity, and imparts the phase change temperature regulation function to enhance the stability of the material.
Smart Images

Figure CN115584243B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal interface materials, and in particular to an interface material having a phase change function and high thermal conductivity and encapsulated worm graphite thermal conductive phase change particles, and a preparation method thereof. Background Art
[0002] Consumer electronic products are accelerating their development towards high power, high integration, thinness and intelligence. As indicators such as integration, power density and assembly density continue to rise, the power consumption and heat generation of electronic devices are rapidly increasing, which has a certain impact on the efficiency, stability and service life of electronic devices. In addition, the rapid development of 5G and 6G communication technologies is a huge test for the heat dissipation capacity of electronic devices.
[0003] Thermal interface materials (TIM) are mainly filled between the heat source and the heat sink to enhance the heat conduction between the two to reduce or prevent overheating. Therefore, high thermal conductivity TIM plays a very critical role in maintaining the efficiency of electronic devices and extending their service life. Traditional TIM mainly improves thermal conductivity by adding thermal conductive fillers to the matrix. However, there is a maximum loading number of thermal conductive fillers, which makes the improvement of thermal conductivity a bottleneck.
[0004] Phase change material (PCM)-based TIM is also a very effective way to dissipate heat through phase change temperature regulation. PCM can use phase change characteristics to store or release heat and provide a constant temperature. It is of great significance to select suitable PCM and use it in TIM. However, leakage during the phase change of PCM (especially solid-liquid PCM) and low thermal conductivity seriously affect the stability of the phase change function.
[0005] The method to improve the thermal conductivity of PCM is usually to add some carbon-containing materials (graphene, carbon nanotubes, expanded graphite, etc.), metal foams and nanoparticles and other fillers. The leakage problem during the phase change process can be effectively solved by adsorption on porous support materials and encapsulation. Worm-like expanded graphite is a fluffy and porous carbon material. Using it as a support material to adsorb PCM can not only improve thermal conductivity but also achieve effective encapsulation of PCM. However, when worm-like expanded graphite is melted and adsorbed on PCM, there is uneven dispersion, resulting in accumulation, agglomeration and other phenomena, resulting in poor adsorption effect, which in turn affects its effect in TIM. Summary of the invention
[0006] In view of the above problems, the present invention provides a thermally conductive phase change particle encapsulated by worm graphite and a thermal interface material with high thermal conductivity and phase change temperature control function. The present invention uses hydrophilically modified worm-like expanded graphite and PCM to obtain phase change thermal conductive particles through vacuum assisted impregnation, and finally compound with other thermal conductive fillers and mix with liquid polymer to obtain the corresponding TIM. The present invention effectively solves the uneven adsorption problem of expanded graphite and PCM through simple hydrophilic modification. The obtained TIM has a double continuous thermal conductive network inside, which effectively improves thermal conductivity and gives the TIM phase change temperature control function.
[0007] One of the purposes of the present invention is to provide a worm-graphite-encapsulated thermally conductive phase-change particle, comprising hydrophilically modified worm-graphite and an organic phase-change material.
[0008] The mass ratio of the organic phase change material to the worm graphite is (0.1-10):1; preferably (2-8.5):1, for example, it can be 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.
[0009] The organic phase change material is at least one of paraffin, stearic acid and polyethylene glycol.
[0010] The hydrophilic modified worm graphite is obtained by mixing a polyamide polyamine epichlorohydrin (PAE) solution with worm graphite and performing vacuum drying.
[0011] The second object of the present invention is to provide a method for preparing the thermally conductive phase change particles, comprising mixing hydrophilically modified worm graphite with anhydrous ethanol, adding an organic phase change material for melting and mixing, and then vacuum impregnating and drying.
[0012] In the preparation method, 0.5 to 2 grams of hydrophilic modified worm graphite is added to every 100 ml of anhydrous ethanol, preferably 0.5 to 1 gram of hydrophilic modified worm graphite is added.
[0013] In the preparation method, the melting and mixing temperature of the hydrophilically modified worm graphite and the organic phase change material is 60-95°C.
[0014] In the preparation method, the vacuum impregnation time is 15 minutes to 3 hours, and the vacuum degree is -0.05 to -0.1 MPa.
[0015] The hydrophilic modified worm graphite is obtained by mixing a polyamide polyamine epichlorohydrin solution with worm graphite and vacuum drying. Preferably, the mixing time is 1 to 5 hours.
[0016] The worm graphite described in the present invention refers to the product of graphite after expansion, and is a loose porous worm-like substance obtained by intercalating natural flake graphite, washing, drying, and high-temperature expansion. The preferred particle size of the worm graphite is 50-100 meshes.
[0017] Preferably, the mass fraction of the polyamide polyamine epichlorohydrin solution is 2 to 15 wt %; more preferably, it is 2 to 12.5 wt %.
[0018] Preferably, the mass ratio of polyamide polyamine epichlorohydrin to worm graphite is 1:(0.01-0.3), preferably 1:(0.01-0.2), for example, it can be 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, etc.
[0019] The third object of the present invention is to provide a thermal interface material, comprising the thermally conductive phase change particles, liquid polymer and thermally conductive filler.
[0020] The thermally conductive filler can be selected from existing thermally conductive fillers in the prior art, preferably one or a combination of two or more of hexagonal boron nitride, aluminum oxide, zinc oxide, aluminum nitride, graphene nanosheets, carbon nanotubes, and diamond.
[0021] The mass ratio of the phase change thermally conductive particles to the thermally conductive filler is (0.5-3):1; preferably (0.5-2.5):1, for example, it can be 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, etc.
[0022] The liquid polymer is at least one of liquid silicone rubber, liquid polyurethane and liquid epoxy resin.
[0023] The ratio of the total mass of the thermally conductive phase-change particles and the thermally conductive filler to the mass of the liquid polymer is (0.1-1):1; preferably (0.2-0.8):1.
[0024] The thermal interface material has high thermal conductivity and phase change temperature regulation functions.
[0025] A fourth object of the present invention is to provide a method for preparing a thermal interface material, comprising uniformly mixing and solidifying the thermally conductive phase change particles, thermally conductive fillers, and liquid polymers in a vacuum environment.
[0026] Preferably, the curing temperature is 80-100° C. and the curing time is 10-30 min.
[0027] The phase-change thermally conductive particles and thermally conductive fillers are compounded, and finally mixed evenly with the liquid polymer through vacuum stirring, and then poured into a mold and cured for a certain period of time to obtain a thermal interface material.
[0028] The basic principle of the present invention is to improve the dispersibility of worm graphite in anhydrous ethanol by hydrophilic modification, so as to facilitate solution impregnation, and then use the loose porous structure of worm graphite to adsorb organic phase change material, reduce the leakage of phase change material during phase change, and give the filler phase change temperature regulation function. Finally, the synthesized phase change thermal conductive filler and thermal conductive filler are compounded, and stirred and mixed with liquid polymer, and solidified to obtain thermal interface material. The distribution of multiple thermal conductive fillers effectively improves the thermal conductivity of thermal interface material.
[0029] Beneficial effects of the present invention:
[0030] 1. The present invention utilizes PAE, a positively charged polymer, which is modified with wormwood graphite through cation π interaction, thereby improving the hydrophilicity of wormwood graphite and effectively improving the mixed adsorption effect of wormwood graphite and organic phase change material in solution. The phase change thermal conductive particles synthesized by this method have both thermal conductivity and phase change temperature regulation functions, and the process is simple and the conditions are mild.
[0031] 2. The present invention compounds phase-change thermally conductive particles and other thermally conductive fillers to establish a dual thermally conductive continuous network, including an "accordion-shaped" thermally conductive network of worm graphite and a thermally conductive network constructed by compounding thermally conductive fillers, thereby effectively improving the thermal conductivity of the thermal interface material.
[0032] 3. Flexible polymer as the matrix material gives TIM the advantage of flexibility and is suitable for a variety of irregular interfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of scanning electron microscopy of unmodified worm-like graphite.
[0034] Figure 2 This is a scanning electron microscope schematic diagram of the phase change filler in Example 1.
[0035] Figure 3 It is a schematic diagram of the double heat-conducting network of the thermal interface material of the present invention.
[0036] Figure 3 In the figure, 1-thermal conductive filler; 2-thermal conductive phase change particles; 3-flexible polymer; 4-thermal conductive phase change network; 5-thermal conductive filler network. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0038] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0039] According to a preferred embodiment of the present invention, the preparation method of the thermally conductive phase change particles includes: mixing the PAE solution with the worm graphite for hydrophilic modification, mixing and dispersing it with anhydrous ethanol after drying, adding the organic phase change material to the melt mixture, assisting vacuum impregnation, and finally introducing it into a mold for curing.
[0040] Comparative Example 1
[0041] 2 grams of 100-mesh worm graphite, 5 grams of paraffin wax, 3 grams of boron nitride and 50 grams of liquid silicone rubber were added into a planetary mixer at the same time, vacuumed and stirred evenly, then poured into a mold, and cured at 100°C for 30 minutes to obtain a liquid silicone rubber thermal interface material containing 20 parts of filler (the total amount of worm graphite, paraffin wax and boron nitride is 20 parts relative to 100 parts of liquid silicone rubber).
[0042] Comparative Example 2
[0043] 2 grams of 80-mesh worm graphite and 200 ml of anhydrous ethanol were directly added to a flask, 8 grams of paraffin wax were added, and the mixture was stirred at 85°C and 500 rpm until it melted, then vacuum impregnated for 2 hours, and dried to obtain a phase-change graphite filler. The obtained 10 grams of phase-change graphite filler, 5 grams of graphene nanosheets, and 25 grams of liquid polyurethane were added to a planetary mixer, vacuumed and stirred to mix evenly, and finally introduced into a mold and cured at 90°C for 1 hour to obtain a liquid polyurethane thermal interface material containing 60 parts of filler (relative to 100 parts of polyurethane, the total amount of thermally conductive phase-change filler and boron nitride is 60 parts).
[0044] Example 1
[0045] 2 grams of 100-mesh worm graphite was put into 500 ml 2.5 wt% PAE solution, stirred and mixed in a beaker for 5 hours for hydrophilic modification and then dried, then put into a flask, added with 200 ml of anhydrous ethanol and stirred and mixed, added with 5 grams of paraffin wax and stirred at 85°C and 500 rpm until melted, then vacuum impregnated for 2 hours, and then dried to obtain a thermally conductive phase change filler. The obtained 7 grams of thermally conductive phase change filler, 3 grams of boron nitride and 50 grams of liquid silicone rubber were added to a planetary mixer, vacuumed and stirred to mix evenly, and finally introduced into a mold and cured at 100°C for 30 minutes to obtain a liquid silicone rubber thermal interface material containing 20 parts of filler (relative to 100 parts of liquid silicone rubber, the total amount of thermally conductive phase change filler and boron nitride is 20 parts).
[0046] Example 2
[0047] 2 grams of 80-mesh worm graphite was put into 500 ml 2.5 wt% PAE solution, stirred and mixed in a beaker for 5 hours for hydrophilic modification and then dried, then put into a flask, added 200 ml of anhydrous ethanol and stirred and mixed, then added 8 grams of paraffin and stirred at 85°C and 500 rpm until melted, then vacuum impregnated for 2 hours, and then dried to obtain a thermally conductive phase change filler. The obtained 10 grams of thermally conductive phase change filler, 5 grams of graphene nanosheets and 25 grams of liquid polyurethane were added to a planetary mixer, vacuumed and stirred to mix evenly, and finally introduced into a mold and cured at 90°C for 1 hour to obtain a liquid polyurethane thermal interface material containing 60 parts of filler.
[0048] Example 3
[0049] 2.5 grams of 100-mesh worm graphite was added to 500 ml of 5wt% PAE solution, stirred and mixed in a beaker for 5 hours for hydrophilic modification and then dried, then added to a flask, 300 ml of anhydrous ethanol was added and stirred, then 20 grams of stearic acid was added and stirred at 85°C and 500 rpm until melted, then vacuum impregnated for 60 minutes, and then dried to obtain a thermally conductive phase change filler. The obtained 22.5 grams of thermally conductive phase change filler, 15 grams of aluminum nitride and 75 grams of liquid epoxy resin were added to a planetary mixer, vacuumed and stirred to mix evenly, and finally introduced into a mold and cured at 100°C for 15 minutes to obtain a liquid epoxy resin thermal interface material containing 50 parts of filler.
[0050] Example 4
[0051] 3 grams of 90-mesh worm graphite was added to 500 ml of 6wt% PAE solution, stirred and mixed in a beaker for 5 hours for hydrophilic modification and then dried, then added to a flask, 500 ml of anhydrous ethanol was added and stirred, 17 grams of polyethylene glycol was added and stirred at 85°C and 500 rpm until melted, then vacuum impregnated for 90 minutes, and then dried to obtain a thermally conductive phase change filler. The obtained 20 grams of thermally conductive phase change filler, 30 grams of zinc oxide and 71.4 grams of liquid polyurethane were added to a planetary mixer, vacuumed and stirred to mix evenly, and finally introduced into a mold and cured at 100°C for 20 minutes to obtain a liquid polyurethane thermal interface material containing 70 parts of filler.
[0052] Example 5
[0053] 2.7 grams of 100-mesh worm graphite was put into 500 ml of 12.5 wt% PAE solution, stirred and mixed in a beaker for 5 hours for hydrophilic modification and then dried, then put into a flask, added with 500 ml of anhydrous ethanol and stirred and mixed, added with 22.3 grams of paraffin wax and stirred at 85°C and 500 rpm until melted, then vacuum impregnated for 60 minutes, and then dried to obtain a thermally conductive phase change filler. The obtained 25 grams of thermally conductive phase change filler, 25 grams of diamond and 62.5 grams of liquid polyurethane were added to a planetary mixer, vacuumed and stirred to mix evenly, and finally introduced into a mold and cured at 90°C for 30 minutes to obtain a liquid polyurethane thermal interface material containing 80 parts of filler.
[0054] Test result explanation
[0055] from Figure 1 It can be seen that the worm graphite is loose and porous, with a multi-layered sheet structure similar to an "accordion". Figure 2 It can be seen that paraffin enters the micropores through the van der Waals force and capillary adsorption between the porous structure of the worm graphite and is impregnated and adsorbed on the worm graphite. Compared with the traditional method of directly mixing the phase change material into the matrix, the worm graphite acts as a supporting material to effectively prevent leakage during the phase change process while improving thermal conductivity. Figure 3 The dual thermal conductive network structure inside the thermal interface material is simulated. One is the phase change thermal conductive network with an "accordion" structure possessed by the phase change thermal conductive particles themselves. The other is a thermal conductive filler network formed by compounding the phase change thermal conductive particles and thermal conductive fillers and overlapping them.
[0056] Table 1 lists the thermal conductivity, phase change enthalpy and leakage rate of the thermal interface materials obtained in Comparative Examples 1-2 and Examples 1-5, as follows:
[0057] Table 1
[0058]
[0059]
[0060] As can be seen from Table 1, the thermal conductivity and phase change enthalpy of Comparative Example 1 are significantly lower than those of Examples 1-4. This is obviously due to the presence of a dual heat conduction network in the examples. One is the phase change heat conduction network formed by the "accordion" structure of the worm graphite adsorbing the phase change material, which gives the interface material a phase change temperature adjustment function, effectively improving the stability of the material in extreme environments. The thermal conductive filler overlaps to form a large-scale heat conduction path to enhance heat conduction. This dual heat conduction network significantly enhances the transmission of phonons in the thermal interface material and enhances heat conduction. The phase change enthalpy of Comparative Example 2 is lower than that of Examples 1-5 because the adsorption effect of the worm graphite on the organic phase change material is significantly improved after the hydrophilic modification.
[0061] In addition, all the products of comparative examples 1-2 and examples 1-5 with the same mass m0 were placed on filter paper at the same time and then placed in an oven and heated to 60°C. Samples were taken out and weighed every 10 minutes until the mass of all samples did not change. Then, the weighing was stopped and the sample mass m was recorded. 平衡 , calculate the leakage rate The leakage rate of comparative example 1 is significantly higher than that of embodiments 1-5. This is because the worm graphite effectively adsorbs the organic phase change material and restrains it through van der Waals force and capillary force, effectively limiting the leakage occurring during the phase change of the organic phase change material, and the stability of its phase change temperature regulation function is significantly improved.
[0062] The present invention modifies worm graphite by polyamide polyamine epichlorohydrin (PAE) solution, then melts and mixes with phase change material, further vacuum-assisted impregnation and drying; then, it is compounded with thermal conductive filler and mixed with liquid polymer by vacuum stirring, and finally solidified to obtain the corresponding thermal conductive phase change thermal interface material. The method and process of the present invention are simple and suitable for large-scale preparation. The obtained material has a double thermal conductive network inside, which not only has much better thermal conductivity than traditional directly mixed samples, but also has high phase change enthalpy to give the material passive temperature regulation ability.
[0063] The above embodiments have described the specific contents of the present invention in detail, but the present invention is not limited to the embodiments, and those skilled in the art can make various equivalent substitutions, such as using different fillers, phase change materials, etc. to change the raw material ratio, using different addition sequences to process the raw material ratio described in the present invention, etc. These equivalent modifications or substitutions are all within the scope of protection claimed in this application.
Claims
1. A worm graphite-encapsulated thermally conductive phase change particle, comprising hydrophilically modified worm graphite and an organic phase change material; the hydrophilically modified worm graphite is obtained by mixing a polyamide polyamine epichlorohydrin solution with the worm graphite and vacuum drying; wherein, The mass ratio of the organic phase change material to the worm graphite is (0.1-10):1; the particle size of the worm graphite is 50-100 meshes; the mass fraction of the polyamide polyamine epichlorohydrin solution is 2-15wt%; the mass ratio of polyamide polyamine epichlorohydrin to worm graphite is 1:(0.01-0.3).
2. The thermally conductive phase change particles according to claim 1, characterized in that: The mass ratio of the organic phase change material to the worm graphite is (2-8.5):
1.
3. The thermally conductive phase change particles according to claim 1, characterized in that: The organic phase change material is at least one of paraffin, stearic acid and polyethylene glycol.
4. A method for preparing the thermally conductive phase change particles according to any one of claims 1 to 3, comprising mixing hydrophilically modified worm graphite with anhydrous ethanol, adding an organic phase change material for melting and mixing, and then vacuum impregnating and drying.
5. The preparation method according to claim 4, characterized in that: The hydrophilic modified worm graphite is obtained by mixing a polyamide polyamine epichlorohydrin solution with worm graphite and performing vacuum drying.
6. The preparation method according to claim 5, characterized in that: The mass ratio of polyamide polyamine epichlorohydrin to worm graphite is 1:(0.01-0.2).
7. The preparation method according to claim 4, characterized in that: Add 0.5-2 g of hydrophilically modified worm graphite per 100 ml of anhydrous ethanol; The melt mixing temperature is 60-95°C, and the vacuum impregnation time is 15min-3h.
8. A thermal interface material, comprising the thermally conductive phase change particles according to any one of claims 1 to 3, a liquid polymer and a thermally conductive filler, wherein the liquid polymer is at least one of liquid silicone rubber, liquid epoxy resin and liquid polyurethane.
9. The thermal interface material according to claim 8, characterized in that: The thermal conductive filler is at least one of hexagonal boron nitride, aluminum oxide, zinc oxide, aluminum nitride, graphene nanosheets, carbon fiber, carbon nanotubes, and diamond; The mass ratio of the thermally conductive phase change particles to the thermally conductive filler is (0.5-3):1; The ratio of the total mass of the thermally conductive phase-change particles and the thermally conductive filler to the mass of the liquid polymer is (0.1-1):
1.
10. The thermal interface material according to claim 9, characterized in that: The mass ratio of the thermally conductive phase change particles to the thermally conductive filler is (0.5-2.5):1; The ratio of the total mass of the thermally conductive phase-change particles and the thermally conductive filler to the mass of the liquid polymer is (0.2-0.8):
1.
11. The method for preparing the thermal interface material according to any one of claims 8 to 10, comprising uniformly mixing and solidifying the thermally conductive phase change particles, thermally conductive fillers, and liquid polymers in a vacuum environment.
12. The method for preparing the thermal interface material according to claim 11, characterized in that: The curing temperature is 80-100°C and the curing time is 10-100 minutes.
Citation Information
Patent Citations
Low-filling high-thermal-conductivity polymer composite material and preparation method thereof
CN113402847A
Preparation method and application of nano-graphite powder with heat storage and conduction functions
CN114031957A